VESPA COMMUNITY JARGON IN PADANG CITY: SOCIOLINGUISTIC REVIEW - Aulia Bayu Depatna Siregar (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
The Vespa community in Indonesia includes many members and lovers. So big, the name of the Vespa community in Indonesia has also been heard to foreign countries. One city that also has a vespa community is the city of Padang. The cohesiveness of the community Vespa lovers is getting bigger. There are not a few national-scale events held in any city, always attended by the Vespa community from all over Indonesia. This article was written to describe the language, types, and meaning of the jargon used by the Vespa community jargon users in the city of Padang. The research data is in the form of the Vespa community's jargon in the city of Padang. The data sources for this research are conversations and dialogues between community members and researchers as communication interactions. Data collected using methods and techniques that have been discovered by previous experts. The first research finding, the language jargon used by the Vespa community in Padang City can be seen from the use of language considered as the Vespa community jargon while the languages used are Indonesian, English and Regional (Minangkabau), Indonesian and English together. Second, the forms can be divided into abbreviations, words, phrases and clauses. Third, it means that the jargon that is formed is not the true meaning of the connotation. Fourth, the vespa community in the city of Padang uses jargon which functions as a tool for communication in familiar places, communication that is relaxed and not tied to anything.